Index Modulation–Aided Mixed Massive Random Access - Liang, Zijie; Zheng, Jianping; Ni, Jie (Frontiers in Communications and Networks, 2021)
In this paper, a mixed massive random access scheme that part of users transmit both common information and user-specific information while others transmit only common information is considered. In this scheme, common information is transmitted by index modulation (IM)-aided unsourced random access (URA) while user-specific information is by IM-aided sourced random access (SRA). Practically, IM-aided URA partitions channel blocks of one transmission frame into multiple groups, and then employs the IM principle to activate only part of the channel blocks in each group. IM-aided SRA allocates multiple pilot sequences to each user and activates only one pilot sequence whose index carries the data information. At receiver, the covariance-based maximum likelihood detection (CB-MLD) is employed to recover the active compressed sensing (CS) codewords of URA and information of SRA jointly. To stitch the common information at different blocks of URA, a modified tree decoder is proposed to take the IM constraint into account. Furthermore, to relax the strict threshold requirement and improve the performance, an iterative CS-detector and tree-decoder is employed to decode the common information, where successive signal reconstruction and interference cancellation are utilized. Finally, computer simulations are given to demonstrate the performance of the proposed scheme.